Buoyancy-driven heat transfer in nanofluid-filled trapezoidal enclosure with variable thermal conductivity and viscosity - Roslan, R.; Saleh, H.; Hashim, I. (Taylor & Francis, 2011)
Heat transfer performance utilizing nanofluids in a trapezoidal enclosure is investigated taking into account variable thermal conductivity and viscosity. Transport equations are modelled by a stream-vorticity formulation, and are solved numerically by the finite difference method. The effects of the Rayleigh number, base angle, volume fraction, and size of nanoparticles on flow and temperature patterns as well as the heat transfer rate are presented. We found that the effect of the viscosity was more dominant than the thermal conductivity, and there is almost no improvement in heat transfer performance utilizing nanofluids.